Pomoc publiczna w gminach stymulatorem rozwoju lokalnego - Kogut-Jaworska, Magdalena (Public Aid in Communities as a Support Local Development, 2009)
Public aid for entrepreneurs is an active form of state's influence on economy. State agencies, through application of such instruments as grants, subsidies or loan guarantees, stimulate positive economic processes and stop negative ones. The goals include reducing differences in regional development through creating new jobs or restructuring in so-called "difficult sectors". Self-government is an active element in network of public support contributing considerably into development of local businesses. This article describes major considerations given to public aid and its role in market economy as well as it focuses on existing possibilities of interventionism by local government through tax reduction and exemptions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 102-110